Pemanfaatan Teknologi untuk Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 (Jurnal AbdiMas Nusa Mandiri, 2020)
The use of technology as a learning medium during the Covid-19 pandemic is an alternative solution to be able to continue to carry out long-distance learning activities. Existing technologies such as Google Meet, Google Classroom and Google Drive strongly support students and teachers and other academics in teaching and learning activities. The use of the facilities provided by Google can be useful for academics. Teaching and learning activities synchronously (synchronous) using video conferencing is an effective way. Not only that, asynchronous learning media using existing Google Classroom facilities such as discussion and chat features are one of the media to support distance learning to keep it running smoothly. The activity was carried out at Majlis Ta'lim Hidayatul Mubtadiin, which consisted of teenagers aged 12-17 years. Based on the questionnaires distributed during the activity, that as many as 96% were able to absorb the material with this distance learning media. So that learning can still be carried out effectively and conducively in the midst of the Covid-19 pandemic.
Keywords: distance learning; google classroom; learning media